All roads lead to ram : the personal history of a spiritual adventurer - Ram, Sruti, 1943- (Monkfish Book Publishing Company, 2021)
"For anyone drawn to spiritual love and devotion, and how to joyfully align one's life to a soulful calling, All Roads Lead to Ram is a captivating and empowering true story. Filled with Hindu deities, ancient temples, glittering festivals, and plenty of danger, it's also entertaining and replete with humor and warmth. Part Indiana Jones adventure story and part spiritual memoir, this book has a remarkable beating heart. Each chapter is a step in Sruti Ram's profound and surprising personal journey. Chapters close with a sutra (lesson) by Sruti Ram himself-offering compassion and guidance grounded in his own powerful experiences and the lessons of the ancient texts. The book also includes Sruti Ram's teachings on Hindu texts and philosophy. For the spiritual seeker, the avid reader, Hindu devotees or neophytes, yoga fans, adventure lovers and armchair travelers, and anyone interested in personal growth and mystical experience, All Roads Lead to Ram is bound to be a sure and rare delight. Illustrated with rare and never-before-seen photos of Neem Karoli Baba, Ram Dass, Sruti Ram himself, and many more"--